In the shadow of the Han : literati thought and society at the beginning of the Southern dynasties - Holcombe, Charles, 1956- (Honolulu : University of Hawaii Press, 1994)
Falling between the great unified empires of the Han and T'ang, the Period of Division (A.D. 220-589) is one of the most overlooked and least understood eras in Chinese history. At the start of the fourth century much of China's traditional heartland fell under the control of ethnic non-Chinese. The remnants of the Chinese court fled to the still somewhat exotic region south of the Yangtze River, where an Eastern Chin dynasty (318-420) was established in virtual exile. The state's ability to command population and other resources had declined sharply from the heights of Han imperial splendor, but it retained considerable influence over most aspects of society, including the economy. This residual state power made possible the rise, through the monopolization of government office, of a new elite class - the literati, or shih-ta-fu.
In this groundbreaking history, Charles Holcombe examines the conditions that produced the literati and shaped their activities during the first of the Southern dynasties, with particular attention to the life and thought of the fourth-century monk Chih Tun (314-366).
The security of the literati's positions in the state, as well as the cooptation process through which they rose to office, encouraged them to neglect the details of actual administrative service and concentrate instead upon peer recognition through the refinement of social graces and through literary, artistic, and philosophical achievements. While the empire hung poised on the brink of ruin, fourth-century literati engaged in round after round of abstruse discussion concerning the ultimate meaning of existence. Their seemingly impractical dalliances blossomed, however, into an age of intellectual and cultural creativity second only to the Warring States period of the late classical era. The Southern dynasties even witnessed significant commercialization and economic growth. Far from the dark ages that their political disunity might imply, China's Southern dynasties reveal themselves to have been great eras of an unexpected kind.
In the Shadow of the Han explores some of the implications of this distinctive Southern dynasty culture.
1. Introduction: Reimagining China -- 2. Refugee State: A Brief Chronicle of the Eastern Chin -- 3. The Socioeconomic Order -- 4. The Institutional Machinery of Literati Ascendance -- 5. Literati Culture -- 6. "True Man": The Power of a Cultural Ideal -- 7. Epilogue: Imperial Restoration.
Includes bibliographical references (pages 191-232) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: China -- History -- Northern and Southern dynasties, 386-589.; Chine -- Histoire -- 386-589 (Dynasties du Nord et du Sud); HISTORY; HISTORY -- Asia -- General; Northern and Southern Dynasties (China); China; Chinees; Cultuurgeschiedenis; Chine -- Histoire -- 386-589 (dynastie du Nord et du Sud); 386-589; History